Nilai-nilai Kemanusiaan dalam Kegiatan Komunitas Sedulur Panther Boyolali - Ramayudha Diky Kurniawan; Achmad Muthali'in (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This research aims to investigate the manifestation of human values within the spectrum of social engagements undertaken by the Sedulur Panther Boyolali Community. Employing qualitative descriptive methods, this study encompasses the participation of key figures, collaborators, and community members. The findings illuminate that the Sedulur Panther Boyolali community holds a central mission: to aid vehicles, particularly Isuzu Panther cars, encountering issues while on the road. Furthermore, this community espouses a profound commitment to humanitarian values, which includes a social agenda and the rehabilitation of residences for citizens deemed unfit for habitation. Beyond their humanitarian endeavors, the Sedulur Panther Boyolali community also engages in regular meetings, communal gatherings, and observes Ramadan by collectively fasting. Through a comprehensive analysis, it can be inferred that the social activities of the Sedulur Panther Boyolali Community harmoniously align with the principles of Pancasila, reflecting a commitment to human values.